Análise da progressão, regressão e atividade de cárie após perda de selante bioativo e fatores associados à autopercepção negativa de saúde bucal em adolescentes - VILARINHO, Adriana Passos Amaral (2022)
Concercing to the minimally invasive treatment, a common technique used to paralyse or even regress the carious lesion is the use of sealants that work as a physical barrier. Bioactive materials have been developed in Dentistry to minimize possible side effects of the technique promoting the remineralization of the dental enamel. The objective of Chapter I was to evaluate the progression/regression of carious lesions in not fully erupted permanent molars treated with conventional sealants or bioactive sealants with pre-reacted glass ionomer (S-PRG) in a split-mouth randomized controlled trial. Sixty second permanent molars in 2 and 3 eruption stage and ICDAS 0 to 2 were treated with the following sealants: self-etching (SPR-G) - Beautisealant (BS) and conventional Fluorshield (FS). After 24 months, each patient was evaluated through the DMF-T, Visible Plaque Index (VPI), Gum Bleeding Index (GBI), Salivary Flow and Buffering Capacity of the Saliva. The treated teeth were evaluated again concerning to the sealant fixation, gravity (ICDAS) and activity (NYVAD) of the carious lesion. Data was analyzed using the Intention-to-Treat Protocol. Wilcoxon, Chi-square and Exact Fisher tests were used (α=5%) and an ordinal regression in the Generalized Estimating Equations module was also used. After 24 months, the patients had a medium age of 15,52 years, 57,89% were females and there was no significant change in DMF-T, VPI and GBI indexes. It was also observed medium values of salivary flow of 1,1774g/min and buffering capacity of 1,4826 Meq/pH/ml. Neither BS nor FS showed some difference in the frequency in fixation of the material (p=0,426), progression/regression (p=0,364), activity (p=0,516), gravity (p=0,740) of the carious lesions. After 24 months, there was no significant difference in clinical performance between bioactive (SPR-G) and conventional sealants. And even great paralisation/regression indexes of carious lesions were observed, the progression of some lesions were not avoided. The objective of Chapter II was to identify factors related to negative self-assessment in oral health (OH) in adolescence and adulthood. Method: 300 questionnaires were answered by adolescent students from the public school system and their guardians. The independent variables were sociodemographic characteristics, myths and beliefs, self-care and oral health care (OH). The dependents were satisfaction with the appearance of teeth and self-assessment OH, both dichotomized into positive and negative. A Pathway Analysis analyzed causal relationships, and data were analyzed by Chi-square or Fisher's Exact tests (p<0.05). A total of 155 adults (average age 38 years and the majority of women, 80.65%) and 145 adolescents (58.57% aged 10 - 11 years and 53.79% male) were analyzed, with 75 % of this sample belonged to the EC economic class and more than 80% used only public health services. There was no relationship between the independent variables and the outcomes in the sample of adolescents. Myths and beliefs are not related to outcomes. Of the adults, women (p = 0.042), individuals who had been to the dentist for more than 1 year (p = 0.022) and those with little knowledge about the use of sealants (p = 0.014 and p = 0.047) were dissatisfied with the appearance of their teeth. The negative self-assessment of OH in adults was predominant in economic classes C-E (p = 0.03), in those who had never heard of sealants (p = 0.012) and in those who found it necessary to brush 3x a day. Conclusion: Only for adulthood, lower socioeconomic status, female gender and little knowledge about preventive measures are related to dissatisfaction with the appearance of teeth and negative self-assessment, but these factors do not have a significant influence on adolescence. A total of 300 questionnaires were answered by adolescent students from the public school system and their guardians. The independent variables were sociodemographic characteristics, myths and beliefs, self- care and OH. The dependents were satisfaction with the appearance of the teeth and OH self-assessment, both dichotomized into positive and negative. Data were analyzed by Chi-square or Fisher's Exact tests (p<0.05) and a Pathway Analysis analyzed causal relationships. Results: A total of 155 adults (mean age 38 years and 80.65% women) and 145 adolescents (58.57% aged 10 - 11 years and 53.79% males) were analyzed, with 75% of this sample belonged to EC economic class and more than 80% used only public health services. There was no relationship between the independent variables and the outcomes in the sample of adolescents. Myths and beliefs are not related to outcomes. Of the adults, women (p = 0.042), individuals who had been to the dentist for more than 1 year (p = 0.022) and those with little knowledge about the use of sealants (p = 0.014 and p = 0.047) were dissatisfied with the appearance of their teeth. The negative self-assessment of OH in adults was predominant in economic classes C-E (p = 0.03), in those who had never heard of sealants (p = 0.012) and in those who found it necessary to brush 3 times a day. Only for adulthood, lower socioeconomic status, female gender and little knowledge about preventive measures are related to dissatisfaction with the appearance of teeth and negative self-assessment, but these factors do not have a significant influence on adolescence.